A scoping review and modelling of predictors of an abnormal Thompson score in term neonates in low-resource settings - Khan Nushrat; Mugwagwa Edna; Cortina-Borja Mario; Catherall Ellie; Fitzgerald Felicity; Chimhuya Simbarashe; Chimhini Gwendoline; Gannon Hannah; Crehan Caroline; Mangiza Marcia; Heys Michelle (Scientific Reports)
Abstract Clinical risk scores, such as Thompson score, are useful alternatives to identify neonatal encephalopathy in low-resource settings where adequate training and equipment are often unavailable. An understanding of the clinical predictors of abnormally high Thompson score values would be beneficial to identify term neonates with suspected neonatal encephalopathy. A scoping review was conducted to identify a set of a priori neonatal and maternal variables associated with neonatal encephalopathy. Next, a prospective study of all term neonates admitted to Sally Mugabe Central Hospital in Zimbabwe between October 2020 and December 2022 was conducted to develop a predictive statistical model of abnormal (> 10) Thompson score. In total 45 articles were identified from searching Medline, Scopus and Web of Science and 10 articles were selected. Five studies were conducted in countries in Asia and five in Africa. Of 6,054 neonates who met the inclusion criteria, 4.06% (n = 246) had an abnormal Thompson score at admission with a case fatality rate of 589 per 1000 admissions. Among these neonates, 90.65% (n = 223) had a low Apgar score (p < 0.001). 40 candidate predictors were identified, of which 20 predictors were selected as the most important. Six risk factors were predictive of neonates at risk of abnormal Thompson score, including low neonatal heart rate (aOR = 0.97), temperature lower than 36.5 °C (aOR = 2.24), head swelling (aOR = 2.19), other maternal risk factors of sepsis excluding offensive liquor and premature rupture of membranes (aOR = 1.97), meconium-stained umbilicus (aOR = 1.79), and not crying at birth (aOR = 2.58). These identified risk factors should be prioritised before conducting a Thompson score assessment in resource-poor settings, and local clinical guidelines should incorporate these into the clinical management of at-risk neonates.